2022
DOI: 10.1001/jamanetworkopen.2022.5018
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 Vaccine Administration and Effectiveness Through October 2021

Abstract: This cohort study reports statewide trends in vaccine administration and vaccine effectiveness in Minnesota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…It should be noted that this study defined cases based on test-positivity only, and it was conducted shortly after vaccine rollout; also, health care workers may differ from the general AI/AN population in terms of socioeconomic status and exposure risk, so comparisons with our results should be made cautiously. In a more recent test-negative design study conducted in Minnesota during Delta predominance, estimated VE among AI/AN persons was lower for COVID-19-associated hospitalization (Pfizer-BioNTech: 72%; Moderna: 76%) than our estimates of VE during Delta predominance [ 34 ]. When stratified by time since vaccination (using a similar time frame as our study, ≤26 vs >26 weeks), results were similar, but our estimates were still greater.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It should be noted that this study defined cases based on test-positivity only, and it was conducted shortly after vaccine rollout; also, health care workers may differ from the general AI/AN population in terms of socioeconomic status and exposure risk, so comparisons with our results should be made cautiously. In a more recent test-negative design study conducted in Minnesota during Delta predominance, estimated VE among AI/AN persons was lower for COVID-19-associated hospitalization (Pfizer-BioNTech: 72%; Moderna: 76%) than our estimates of VE during Delta predominance [ 34 ]. When stratified by time since vaccination (using a similar time frame as our study, ≤26 vs >26 weeks), results were similar, but our estimates were still greater.…”
Section: Discussionmentioning
confidence: 86%
“…Traditional knowledge, histories, language, and values are irreparably lost with every tribal elder who has succumbed to COVID-19, and these losses are borne by entire communities [ 4 ]. Previous studies have reported reduced VE in older hospitalized adults [ 18 , 34 ]. Although we also observed that VE point estimates decreased with age among inpatients, confidence intervals overlapped, and there were no significant differences in VE by age group.…”
Section: Discussionmentioning
confidence: 99%
“…The common data files also include information on whether an individual experienced homelessness or incarceration within the prior year. Each row in the common data file is dedicated to an individual and includes the following data: age, sex, race/ethnicity, SARS-CoV-2 and influenza testing date and result, COVID-19 vaccination date and type, specific comorbid medical conditions, and neighborhood level characteristics (i.e., social vulnerability index and rurality) at the zip code level [ 15 – 17 ]. Because patients may be seen at multiple health systems, each patient is assigned to one health system based on the following: availability of race/ethnicity data, intensity of care in the last 12 and 36 months (defined by number of blood pressures documented in the patient record), and year of last diagnosis in the EHR.…”
Section: Methodsmentioning
confidence: 99%
“…The hospitalization file includes admission and discharge dates, and a link to the site-specific common data file at the patient level. Data on homelessness, incarceration, death, and vaccinations are linked to MNEHRC data using a secure privacy-preserving record linkage (PPRL) process [ 11 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2021 and 2022, the availability of COVID-19 vaccinations has increased (15,16), which could be effective to reduce the number of infections and severity of cases (17). A retrospective study published in 2023 found that mortality rates among patients undergoing liver transplantation during vaccination period (September 2021 to March 2022) have equalized with pre-COVID-19 (18).…”
Section: Did Covid-19 Vaccinations Improve Outcomes After Hpb Surgery?mentioning
confidence: 99%